PREPARATION AND CHARACTERIZATIONS OF NEW BIOMATERIALS BY ANTHOCYANINS ADSORPTION ON HYDROXYAPATITE-BASED MATERIALS - BARABÁS, Réka; MUNTEAN, Norbert; SZABÓ, Gabriella Stefánia; MAURER, Krisztina; BIZO, Liliana-Antonela (Studia Universitatis Babeș-Bolyai Chemia, 2017)
Anthocyanins (ACNs) are water-soluble plant pigments belonging to the group of flavonoids, with antioxidant, anti-inflammatory and antibacterial activity. The antioxidant activities of extracts from berries and hibiscus were tested with the Briggs–Rauscher method. Adsorption of anthocyanins on biomaterials is a method for their stabilization. Hydroxyapatite (HAP) doped with inorganic silica has an increased specific surface, porosity and chemical reactivity. Anthocyanins from extracts of different berries were adsorbed on hydroxyapatite-based materials. The adsorption and desorption capacity of hydroxyapatite-based materials were measured and the adsorption capacity of different anthocyanin extracts were compared. It was concluded that the highest adsorption capacity and efficiency were obtained in the case of blueberry. Based on the results of the desorption experiments, it has been proven that HAP-Si-blueberry is more adequate to obtain a retard effect, despite the fact that the antioxidant activities of blueberry and blackcurrant are similar.